On Descartes' passive thought the myth of Cartesian dualism - Marion, Jean-Luc, 1946- (The University of Chicago Press, 2018)
'On Descartes' Passive Thought' is the culmination of a life-long reflection on the philosophy of Descartes by one of the most important living French philosophers. In it, Jean-Luc Marion examines anew some of the questions left unresolved in his previous books about Descartes, with a particular focus on Descartes's theory of morals and the passions. Descartes has long been associated with mind-body dualism, but Marion argues here that this a historical misattribution, popularized by Malebranche and popular ever since both within the academy and with the general public.